The integration of proportion and cell counts of stromal, not intratumoral, PD-1+ tumor-infiltrating lymphocytes has prognostic significance in esophageal squamous cell carcinoma. Issue 1 (12th May 2020) - Song, Qingkun; Shi, Feng; Xiao, Shuo; Li, Yuchen; Zhao, Yanjie; Chang, Hong
Summary: The present study aimed to investigate the prognostic effect of intratumoral and stromal exhausted tumor-infiltrating lymphocytes (TILs) on operable esophageal cancer patients. We performed a retrospective cohort study by consecutively recruiting 142 patients with esophageal cancer. The proportion and cell counts of intratumoral and stromal PD-1 + TILs in tumor microenvironment were independently evaluated by two pathologists. Neither proportion nor cell counts of intratumoral PD-1 + TILs was associated with prognosis ( p > 0.05). However, patients with the proportion of stromal PD1 + TILs >20% had the median overall survival (OS) at 19 months, significantly longer than those with the proportion = 20%. The adjusted hazard ratio (HR) was 1.49 (95%CI 0.82, 2.69). Patients with cell counts of stromal PD1 + TILs = 18/ high-power field (HPF) had the median disease-free survival (DFS) at 10 months. However, patients with cell counts>18/HPF had the median DFS at 48 months ( p = 0.037), and the adjusted HR was 0.59 (95%CI 0.35, 1.01). Compared with patients with proportion = 20% and cell counts >18/HPF of stromal PD1 + TILs, patients with proportion = 20% and cell counts = 18/HPF, proportion >20% and cell counts >18/HPF, and proportion >20% and cell counts = 18/HPF, had the adjusted HRs increased to 3.73, 3.36 and 3.99 for DFS ( p for trend being 0.030) and the adjusted HRs increased to 2.95, 3.64 and 3.82 ( p for trend being 0.015) for OS, respectively. The integration of proportion and cell counts of PD-1 + stromal TILs has a significant association with the relapse and overall survival of esophageal cancer patients. Further prospective studies are warranted.